Glial cell regulation of neuronal activity and blood flow in the retina by release of gliotransmitters - Newman, Eric A. (Philos Trans R Soc Lond B Biol Sci, 2015)
Astrocytes in the brain release transmitters that actively modulate neuronal excitability and synaptic efficacy. Astrocytes also release vasoactive agents that contribute to neurovascular coupling. As reviewed in this article, Müller cells, the principal retinal glial cells, modulate neuronal activity and blood flow in the retina. Stimulated Müller cells release ATP which, following its conversion to adenosine by ectoenzymes, hyperpolarizes retinal ganglion cells by activation of A1 adenosine receptors. This results in the opening of G protein-coupled inwardly rectifying potassium (GIRK) channels and small conductance Ca(2+)-activated K(+) (SK) channels. Tonic release of ATP also contributes to the generation of tone in the retinal vasculature by activation of P2X receptors on vascular smooth muscle cells. Vascular tone is lost when glial cells are poisoned with the gliotoxin fluorocitrate. The glial release of vasoactive metabolites of arachidonic acid, including prostaglandin E(2) (PGE(2)) and epoxyeicosatrienoic acids (EETs), contributes to neurovascular coupling in the retina. Neurovascular coupling is reduced when neuronal stimulation of glial cells is interrupted and when the synthesis of arachidonic acid metabolites is blocked. Neurovascular coupling is compromised in diabetic retinopathy owing to the loss of glial-mediated vasodilation. This loss can be reversed by inhibiting inducible nitric oxide synthase. It is likely that future research will reveal additional important functions of the release of transmitters from glial cells.